The Herbert Virtual Museum. (8th September 2013) - Petridis, Panagiotis; Dunwell, Ian; Liarokapis, Fotis; Constantinou, George; Arnab, Sylvester; de Freitas, Sara; Hendrix, Maurice
Abstract : In recent years, virtual reality and augmented reality have emerged as areas of extreme interest as unique methods for visualising and interacting with digital museum artefacts in a different context, for example, as a virtual museum or exhibition, particularly over the Internet. Modern cultural heritage exhibitions have evolved from static to dynamic exhibitions and challenging explorations. This paper presents two different applications developed for the Herbert Museum and Art Gallery that make the user's experience more immersive, engaging, and interactive. The first application utilizes mobile phone devices in order to enrich the visitors experience in the museum, and the second application is a serious game for cultural heritage and in particular for museum environments focusing on the younger visitors.